Response Time and Therapeutic Communication Capability of Nurses on Patient Satisfaction: - - Subekti, Imam; Ariyani, Imelda Aqhna; Sulastyawati, Sulastyawati (Poltekkes Kemenkes Malang, Campus III Blitar, 2024)
Lack of response time and therapeutic communication by nurses cause patient and family dissatisfaction with services at the hospital. This study aimed to determine the relationship between response time and nurses' therapeutic communication skills on patient satisfaction in the emergency room at Lavalette Hospital, Malang, in May 2024. This research method uses a cross-sectional design. The research sample was patients treated in the emergency room, with a total of 92 respondents. The sampling method used accidental sampling. The data collection method observes the time it takes for nurses to carry out initial actions and questionnaires on nurse therapeutic communication and patient satisfaction. Bivariate analysis used Spearman-Rho, and multivariate analysis used multiple linear regression with a p-value <0.05. The results of the bivariate analysis showed that the p-value for response time was 0.000 and therapeutic communication was 0.001, so it could be concluded that there was a relationship between response time, therapeutic communication, and patient satisfaction in the emergency room at Lavalette Hospital, Malang. Nurses' response time and therapeutic communication skills should be maintained and improved in providing services in hospitals, especially in the emergency room, to prevent problems from arising that could impact patient satisfaction.